Children Born From Non-Religious Marriages From The Perspective Of Child Protection Law And Psychology - Ika Dewi Sartika Saimima; Yuarini Wahyu Pertiwi (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2026)
Marriages of different religions occur due to the conditions of Indonesian society, which is composed of different races, cultures, tribes, and languages. The prohibition of non-religious marriages through the Marriage Act No. 1 of 1974 eventually became a widespread controversy, especially after the publication of the Supreme Court Ordinance No. 2 of 2023 on Guidelines for Judges in Judging Applications for Registration of Marriages between Different Religions and Beliefs. The ban affects the social and psychological needs22ws of children born to different religious couples. The publication of the Supreme Court editorial resulted in unregistered marriages, and the legal status of children who were eventually born from marriages of different religions had difficulties marrying and adapting to their environment. Psychologically, children experience anxiety due to their parents' condition and influence when interacting or socializing. As for the aspects of anxiety, they include emotional, physiological, cognitive, and behavioral anxieties.